A Blended Mobile Learning Context Oriented Model in a Cloud environment applied to a RE course - Moreira, Fernando (2016)
The increasing number of mobile devices on day-to-day of the general population and particularly among youth people, leads to the emergence of new paradigms in several areas of activity, particularly in education. As an example of a new paradigm in the teaching / learning process can be invoked the mobile learning supported by a cloud environment and by Bloom Taxonomy. In this paper and in the context of three-year courses Bologna Process European Degree structure at school, in Portugal, following the Curriculum Guidelines for Undergraduate Degree in a Information Systems from ACM/AIS, we intend to test Mobile Google Docs system, aligned with Bloom's Taxonomy, in our BML Context Oriented (BML-CO) model into a Requirement Engineering (RE) course